Sonographic Risk Stratification Systems for Thyroid Nodules as Rule-Out Tests in Older Adults - Grani, Giorgio (Cancers (Basel), 2020)
SIMPLE SUMMARY: The use of risk-stratification systems for thyroid nodules based on ultrasound features may reduce the number of biopsies to be performed. The aim of our study was to assess the diagnostic performance of these systems in different age groups. We confirmed that all systems had a significant discriminative performance in all age groups. The system proposed by the American College of Radiology was the best performing one, but all risk-stratification systems could avoid a sizable number of biopsies when applied as rule-out tests (to exclude malignancy) in elderly patients. ABSTRACT: Ultrasonographic risk-stratification systems (RSS), including various Thyroid Imaging Reporting and Data Systems (TIRADS), were proposed to improve reporting and reduce the number of fine-needle aspiration biopsies. However, age might be a confounder since some suspicious ultrasonographic features lack specificity in elderly patients. We aimed to investigate whether the diagnostic performance of the RSS varied between age groups. All patients consecutively referred for thyroid biopsy between November 1, 2015, and March 10, 2020, were included. The malignancy risk of each nodule was estimated according to five RSS: the American Association of Clinical Endocrinologists/American College of Endocrinology/Associazione Medici Endocrinologi guidelines, the American College of Radiology (ACR) TIRADS, the American Thyroid Association guidelines, the European TIRADS, and the Korean TIRADS. Overall, 818 nodules (57 malignant) were evaluated. The malignancy rate was higher in patients ≤ 65 years (8.1%) than in patients > 65 years (3.8%; p = 0.02). All RSS confirmed a significant discriminative performance in both age groups, with a negative predictive value of 100% in patients > 65 years, although specificity was lower in older patients. The ACR TIRADS was the best performing in both age groups. RSS could avoid a sizable number of biopsies when applied as rule-out tests in elderly patients.